The effects of glucocorticoids and immunosuppressants on cancer outcomes in checkpoint inhibitor therapy - Bruera, Sebastian; Suarez-Almazor, Maria E. (Frontiers in Oncology, 2022)
The emergence of checkpoint inhibitors has created a paradigm shift for the treatment of various malignancies. However, although these therapies are associated with improved survival rates, they also carry the risk of immune-related adverse events (irAEs). Moderate to severe irAEs are typically treated with glucocorticoids, sometimes with the addition of immunosuppressants as steroid-sparing therapy. However, it is unclear how glucocorticoids and immunosuppressants may impact cancer survival and the efficacy of immune checkpoint therapy on cancer. In this narrative review, we discuss the effects of glucocorticoids and immunosuppressants including methotrexate, hydroxychloroquine, azathioprine, mycophenolate mofetil, tumor-necrosis factor (TNF)-inhibitors, interleukin-6 inhibitors, interleukin-1 inhibitors, abatacept, rituximab, and Janus kinase inhibitors (JAKi) on cancer-specific outcomes in the setting of immune checkpoint inhibitor use.